2021
DOI: 10.20885/psikologika.vol26.iss1.art3
|View full text |Cite
|
Sign up to set email alerts
|

Gangguan Psikologis dan Kesejahteraan Psikologis pada Mahasiswa Baru

Abstract: First-year university students are vulnerable to certain psychological disorders. Psychological Well-Being (PWB) is one of the resources they can use to face academic challenges. However, research focusing to identify PWB as protective factor among first-year university students is still rare. This study employs quantitative method involving 151 respondents from the Faculty of Psychology of University X in West Java. It uses a PWB scale composed by Ryff and Self Report Questionnaire (SRQ-20). It also employs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
2
0
2
Order By: Relevance
“…The results of both types of reliability indicated that the SRQ-20 as a measuring instrument can be trusted. This finding is also in line with several previous studies stated that the SRQ-20 has a good reliability (Kootbodien et al, 2015;Prasetio et al, 2019;van der Westhuizen et al, 2015) (Kootbodien et al, 2015;Prasetio et al, 2019;Triwahyuni & Prasetio, 2021;van der Westhuizen et al, 2015).…”
Section: Prasetio Et Al Psychometric Properties Of Self-reportsupporting
confidence: 93%
“…The results of both types of reliability indicated that the SRQ-20 as a measuring instrument can be trusted. This finding is also in line with several previous studies stated that the SRQ-20 has a good reliability (Kootbodien et al, 2015;Prasetio et al, 2019;van der Westhuizen et al, 2015) (Kootbodien et al, 2015;Prasetio et al, 2019;Triwahyuni & Prasetio, 2021;van der Westhuizen et al, 2015).…”
Section: Prasetio Et Al Psychometric Properties Of Self-reportsupporting
confidence: 93%
“…Environmental mastery refers to a person's belief in making his surroundings meet his needs (Triwahyuni & Prasetio, 2021). This study's dimension of environmental mastery possessed by migrant high school students is relatively high.…”
Section: Discussionmentioning
confidence: 89%
“…Kesejahteraan psikologis yang rendah dapat memberikan dampak negatif pada siswa, mengingat kesejahteraan psikologis dapat menjadi faktor protektif dari indikasi gangguan mental (Triwahyuni & Prasetio, 2021). Berdasarkan hasil Riskesdas 2018, di Provinsi Bali terdapat peningkatan prevalensi gangguan mental emosional sebesar 4% pada penduduk berusia >15 tahun dibandingkan dengan hasil Riskesdas 2013 sebelumnya.…”
Section: Latar Belakangunclassified